That's What I like: A Study of Consumer Behavior on Purchase Intention Towards Pepsi - Juliana Johari; Ee Ming Tan; Syaza Najihah; Jia Yin Tan; Fatmah Yousef Alsallal; Suzarmie Supilit; Dalal Alfarhan (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
PepsiCo's Pepsi is one of the leading brands in the enormous soft drinks market. The company has gone through bankruptcy and survived. Pepsi is a common name globally to most age groups with a wide range of target demographics. This paper examines how five key factors, namely perceived product quality, perceived price affordability, brand awareness, perceived ease of access, and brand loyalty, lead to Pepsi's customer purchase intention in Malaysia and Kuwait. We tested hypotheses with 103 participants. The findings showed that perceived product quality and brand loyalty significantly correlate with purchase intention. Our findings provide new insights and contribute to consumer behavior.    Keywords: Brand Awareness, Brand Loyalty, Customers Perception, Purchase Intention, Perceived Ease of Access, Perceived Price Affordability, Perceived Product Quality